Comparative study of wold and lowland situated small watercourses from fishbiological aspect - Takács, Péter (Acta Agraria Debreceniensis, 2007)
Fishbiological research was held on 10 small watercourses, especially on the streams of woldy region of the southern foot of the Bükk-mountains and on the creeks of the lowland Borsodi-Mezőség in 2004. 7475 specimens of 34 species were caught as the result of our surveys on 28 sampling sites. Significant differences were found between fish stocks living in wold and lowland situated sampling sites.Nevertheless on the border of the hilly and lowland regions continous transition observed in the composition of fishstocks. Using Ind Val 2.0 statistical software indicator species appointed of the stocks of wold situated samling sites in “natural” and in “disturbed” states, and of the lowland situated sampling sites.